2017
DOI: 10.14808/sci.plena.2017.049915
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem computacional de um conversor de energia das ondas em energia elétrica do tipo Coluna de Água Oscilante (CAO) considerando dados de estado do mar

Abstract: O presente estudo utiliza dados simulados de estado de mar, obtidos através do modelo TOMAWAC, como condição de contorno para a simulação numérica do princípio de funcionamento de um conversor de energia das ondas do mar em energia elétrica do tipo Coluna de Água Oscilante (CAO). Para isso foi considerada uma região próxima à costa de Rio Grande, RS, onde os dados de altura significativa (Hs) foram usados para determinar a variação de velocidade vertical (w) da superfície livre do mar. Então, adotando um model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…2c), several area ratios were used to evaluate the localized pressure drop influence on static pressure. The dimensions used are based on the values presented by De Oliveira et al (2017), being showed in Tab. 1.…”
Section: Computational Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…2c), several area ratios were used to evaluate the localized pressure drop influence on static pressure. The dimensions used are based on the values presented by De Oliveira et al (2017), being showed in Tab. 1.…”
Section: Computational Domainmentioning
confidence: 99%
“…The Piston Methodology was also used by Barakaz and El Marjani (2016), where a onedimensional model was used to describe the OWC behavior. In De Oliveira et al (2017) this methodology was used in the verification of an OWC two-dimensional computational model. These studies have proved the effectiveness of the piston methodology in representing the physical phenomena involved in the operation of this type of converter.…”
Section: Introductionmentioning
confidence: 99%